Influence of NaCl on Phase Development and Corrosion Resistance of Portland Cement - Byung-Hyun Shin; Miyoung You; Jinyong Park; Junghyun Cho; Seongjun Kim; Jung-Woo Ok; Jonggi Hong; Taekyu Lee; Jong-Seong Bae; Pungkeun Song; Jang-Hee Yoon (Crystals)
Portland cement is one of the most widely used construction materials employed in both large-scale structures and everyday applications. Although various materials are often added during production to enhance their performance, NaCl can be introduced in the process for various reasons. Despite this issue, existing studies lack sufficient quantitative data on the effects of NaCl on cement properties. Therefore, this study aims to investigate the physical and chemical degradation mechanisms in cement containing NaCl. Cement specimens were prepared by mixing cement, water, and NaCl, followed by stirring at 60 rpm and curing at room temperature for seven days. Microstructural changes as a function of the NaCl concentration were analyzed using scanning electron microscopy (SEM), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS). Electrochemical properties were evaluated via open-circuit potential (OCP) measurements, electrochemical impedance spectroscopy (EIS), and potentiodynamic polarization tests. The results indicate that increasing the NaCl concentration leads to the formation of fine precipitates, the degradation of the cement matrix, and the reduced stability of major hydration products. Furthermore, the electrochemical analysis revealed that higher NaCl concentrations weaken the passive layer on the cement surface, resulting in an increased corrosion rate from 1 × 10−7 to 4 × 10−7 on the active polarization of the potentiodynamic polarization curve. Additionally, the pitting potential (Epit) decreased from 0.73 V to 0.61 V with an increasing NaCl concentration up to 3 wt.%. This study quantitatively evaluates the impact of NaCl on the durability of Portland cement and provides fundamental data to ensure the long-term stability of cement structures in chloride-rich environments.